PENYULUHAN TENTANG DASAR ILMU PERUNDANG-UNDANGAN BAGI KARYAWAN PT. SULTAN PERMATA INDONESIA DI TANGERANG SELATAN - Abdur Rahim; Tsani Nurul Hanifah; Olive Nabata; Najmi Shabrina; Nazwa Alaida Salsabila; Daryino Daryino; Wasto Wasto; Fitri Nur Anisa (Jurnal Abdimas Bina Bangsa, 2023)
The action of devotion to the community was intended to understand the awareness of the community of the importance of legal awareness of the study of transitory laws. The method used for transitioning this understanding by counseling communities set aside for Indonesian government officials the basis of the study of transitations. The result of this activity is that people get clear information on the basis of the study of legislation and can be implemented into everyday life. As for the reform state which is considered most realistic, giving debriefing through delivery of materials and debriefing activities that are thought to be useful to workers. The student's creativity program of community service is a tool for the student to perform community service. As for the performance of devotion to the public using the face-to-face learning methods presented by the tinker